Organic maize and bean farming enhances free-living nematode dynamics in sub-Saharan Africa - Atandi, J.; Adamtey, N.; Kiriga, A.; Karanja, E.; Musyoka, M.W.; Matheri, F.; Tanga, C.M.; Coyne, D.; Fiaboe, K.; Bautze, D.; Haukeland, Solveig (Elsevier, 2022)
Despite their important ecological roles for soil health and soil fertility, free-living nematodes (FLN) have received relatively limited research attention. The present study evaluated the community structure and diversity of FLN in a field setting. The experiments were conducted in on-farm and on-station field plots sown to maize (Zea mays) and beans (Phaseolus vulgaris) under four cropping practices. These farming systems included organic (compost and biopesticide use), conventional (synthetic fertilizer and pesticide applications), farmer practice (organic and synthetic amendments) and a control (non-amended plots). Nineteen genera of free living nematodes, belonging to bacterivores, fungivores, omnivores and predators were recorded. Among these, bacterivores (Cephalobidae and Rhabditidae) were the most dominant group in the organic systems when compared to the conventional and control systems. Farming systems influenced the abundance and diversity of free living nematodes, with the organic farming system having higher values of maturity, enrichment and structural indices than other farming systems. This would indicate greater stability in soil health and improved soil fertility. This implies that the organic farming systems play a key role in improving the biodiversity and population buildup of FLN, compared with other systems. Our study helps to improve our understanding of how farming systems influence soil biodynamics, while studies on the longer-term effects of organic and conventional farming systems on the build-up or reduction of free living nematodes for improved ecosystem services are needed.